2009
DOI: 10.1007/s11595-009-2295-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistance behavior of vinylester composites filled with glass-carbon hybrid fibers

Abstract: Vinylester (bismethacryloxy derivative of a bisphenol-A type EP resin, VE) composites with glass-carbon hybrid fibers (CF-GF) weight fraction of 50%, were prepared by the compress molding method. The distribution of carbon fiber in the hybrids was observed by stereomicroscope. The electrical resistance behavior of the composites filled with different carbon fiber (CF) weight contents (0.5% to 20%) was studied. The experimental results show that the electrical resistance behaviors of CF-GF/VE composites are dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…When we choose tools, the selected tools are not only to have the required processing capacity, and should be the optimal tool in certain optimization goals. The surface roughness is an important parameter for measuring processed surface quality [5][6], appropriate tool play an important role on surface roughness. Therefore, giving full play to the excellent properties of cutting tool and achieve desired cutting effect, we must choice reasonable tool according to the specific object.…”
Section: Introductionmentioning
confidence: 99%
“…When we choose tools, the selected tools are not only to have the required processing capacity, and should be the optimal tool in certain optimization goals. The surface roughness is an important parameter for measuring processed surface quality [5][6], appropriate tool play an important role on surface roughness. Therefore, giving full play to the excellent properties of cutting tool and achieve desired cutting effect, we must choice reasonable tool according to the specific object.…”
Section: Introductionmentioning
confidence: 99%
“…Both species were demonstrated to adsorb onto the metal surface but contradictory effects (suppressing or accelerating) were claimed on the corrosion of Zr. 26,27 It has also been reported that the presence of H 2 O 2 reduces the corrosion resistance of thermally oxidized Zr5Ti where surface oxides are mostly composed of ZrO 2 . 29 No studies have been reported on the combined effect of H 2 O 2 and albumin in terms of corrosion and corrosion products.…”
mentioning
confidence: 98%
“…25 The increased corrosion rates induced by H 2 O 2 and albumin highlights the complex roles that biomolecules have in mediating corrosion at the implant surface. More recently, very limited work has been carried out on the role of organic species including glycine 26 and albumin 27,28 on corrosion of Zr. Both species were demonstrated to adsorb onto the metal surface but contradictory effects (suppressing or accelerating) were claimed on the corrosion of Zr.…”
mentioning
confidence: 99%